Evaluating The Influence Of Satisfaction As A Mediator On Generation Z’s Loyalty To Airline ‘Aa’ - Ruslim, Tommy Setiawan; Soelaiman, Lydiawati; Suryawan, Ian Nurpatria (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Aviation transportation services are something that people really need nowadays to make it easier to move from one place to another. The aviation industry in Indonesia is experiencing a surge in demand from the local community. The importance of customer loyalty in the aviation industry aims to maintain the existence of an airline or is even expected to be able to improve it so that it can become a superior airline in the aviation industry. Generation Z was found to prioritize air transportation as the main thing and factor in traveling. In realizing an optimal domestic airline aviation industry,